ICT and Changing Mindsets in Education. - Toure, Kathryn (Langaa RPCIG, 2008)
The debate is no longer whether to use information and communication technologies (ICT) in education in Africa but how to do so, and how to ensure equitable access for teachers and learners, whether in urban or rural settings. This is a book about how Africans adopt and adapt ICT. It is also about how ICT shape African schools and classrooms. Why do we use ICT, or not? Do girls and boys use them in the same ways? How are teachers and students in primary and secondary schools in Africa using ICT in teaching and learning? How does the process transform relations among learners, educators and kno.